PERILAKU KEUANGAN WIRAUSAHA PADA INDUSTRI PARIWISATA: STUDI KOMPARATIF GENERASI X, Y DAN Z - Ni Made Rukmiyati (JURNAL KEPARIWISATAAN, 2022)
This study aims to determine the differences in financial behavior among generations X, Y, and Z. This study uses the Kruskal-Wallis test to examine differences in financial behavior. Based on the results of the Kruskall-Wallis test, it is concluded that there are differences in financial management between Generations X, Y, and Z, with a Chi-Square value of 12,579 and an Asympt. Sig. of 0.002 < (0.05). Generation differences will also lead to differences in information in each generation that can affect financial behavior. This study supports the Theory of Planned Behavior, which states that humans behave in a conscious way by considering relevant information.